ABOUT THE TRANSLATION OF PROVERBS AND SAYINGS - Asatullayevna , Ibragimova Lola (Eurasian Journal of Academic Research, 2022)
Proverbs are very broad in content. This feature allows large semantic shifts to the article itself, so that a single article can be used in different contexts in different contexts. That fact must be taken into account. Articles clarified between English and Uzbek folk proverbs, as well as proverbs of other nations with their features of glorifying and exemplifying universal qualities, can be created independently as a result of the general progress in the life of each nation, on the one hand, and through the lives of other peoples The theme of proverbs, and sayings people have always loved and respected their homeland and fought hard against the enemies of the Motherland, its traitors and invaders. That is why in such articles as "The nightingale loves the nature, the man loves the Motherland", "If your motherland is alive, your color will not be straw", "The beggar of the homeland - the beggar of the shroud" finds its concise logical conclusion. Many of the proverbs express true human qualities such as courage, bravery, generosity, justice, honesty, pure love, loyalty, kindness, and high generosity.